ANALISIS PENGARUH KUALITAS JASA DAN PERSEPSI NILAI PELANGGAN TERHADAP KEPUTUSAN PELANGGAN DALAM MEMILIH LAYANAN LISTRIK PRABAYAR PADA PLN RIAU (Jurnal Tepak Manajemen Bisnis, 2014)
The study aims to determine the effect of each factor of the quality of services , both directly and through perceived value , the decision to choose. Research using 200 respondents , selected by purposive sampling method , using questionnaires in data collection . Structural equation modeling analysis method using the Partial Least Square that does not need to meet the various requirements of data assumptions. . The evidence suggests , predictive models of service quality to the perception of value in the criteria that tend to moderate and moderately well . But the only factor of professionalism and skill , reliability and trustworthiness , accessibility and flexibility as well as a significant positive effect , with professionalism and skill as the most important factor heightens the perception of value . On the other hand , only the accessibility and flexibility as the sole factor in the quality of services that are directly significant , but with a negative influence on the decision to choose . The good predictive models perception of shared values to the seven factors of service quality , more because of the perceived value of a positive role in pushing the decision to choose . Increased availability of electric power capacity , the operating system that supported the process of professional services , can enhance perceptions of service quality and value . So that will strengthen the decision-making customers choose prepaid electricity service PLN Pekanbaru Area .Keywords : service quality , perceived value , the decision of choosing , prepaid electricity , PLN Pekanbaru Area.